Multiexponential Analysis of the Water T2‐Relaxation in the Skeletal Muscle Provides Distinct Markers of Disease Activity Between Inflammatory and Dystrophic Myopathies. Issue 1 (5th August 2020) - Araujo, Ericky C. A.; Marty, Benjamin; Carlier, Pierre G.; Baudin, Pierre‐Yves; Reyngoudt, Harmen
Abstract : Background: The monoexponential water T2 (T2‐mono ) is a proven biomarker of disease activity in neuromuscular disorders (NMDs). However, it lacks specificity, being elevated in the presence of several pathological processes and pathomorphological alterations in the muscle tissue. Purpose: To investigate the multiexponential behavior of the water T2 ‐relaxation in the skeletal muscle of NMD patients, aiming to identify more sensitive and specific biomarkers of disease activity. Study Type: Retrospective case–control. Population: Thirty Duchenne muscular dystrophy and 114 inclusion body myositis patients and 55 control subjects. Field Strength/Sequence: 3T/Single‐voxel proton spectroscopy ( 1 H‐MRS) and multispin‐echo (MSE) imaging. Assessment: Water T2 ‐decay curves generated from 1 H‐MRS data acquired at 14 echo‐times were fitted to mono‐ and biexponential models and the adjusted R 2 of each fit was computed. Additionally, T2 spectra were generated from a regularized inverse Laplace transform. For comparison, water T2 maps were generated from the MSE data. The performances of the different variables at identifying patients were assessed via receiver operating characteristic (ROC)‐curve analysis. Statistical Tests: Chi‐square, Kruskal–Wallis, and Mann–Whitney with Bonferroni correction for multiple comparisons. Results: T2‐mono was elevated in patients ( P <0.05), but could not distinguish inclusion body myositis (IBM) from Duchenne muscular dystrophy (DMD). While 79% of IBM data presented a biexponential behavior, this was only 16% and 10% for DMD and control data, respectively ( P <0.05). All T2 spectra presented an intermediate‐T2 peak characterized by an elevated T2 in patients ( P <0.05) and by a relative fraction that was abnormally smaller in IBM patients ( P <0.05). Also, a long‐T2 peak was exclusively observed in IBM patients. A combination of T2 ‐spectrum variables performed best at identifying patients. Data Conclusion: T2 spectra not only provided more sensitive and specific markers of disease presence than the T2‐mono, but also allowed distinguishing IBM from DMD patients. This must reflect distinct predominant pathological alterations between these diseases, suggesting that these markers provide additional pathophysiological/histopathological information that are missing from T2‐mono . Level of Evidence: 3 Technical Efficacy Stage: 3